Memahami Pengembangan Proyek Penguatan Profile Pelajar Pancasila - Lao, Hendrik A.E; Syahputra, Andrian Wira; Neno, Yoksan Edison (Sekolah Tinggi Teologi Real Batam, 2024)
This training is to provide understanding to school principals and teachers about the importance of developing the Pancasila student profile which is currently in effect in the independent curriculum. The targets for this Community Service group activity are leaders, teaching staff and education staff at SDN Oeteas, Rote Ndao Regency. The activity was carried out for 2 days from 7-8 September 2023. The main material presented was to provide education and workshops through assisting Pancasila student profile project creators and providing practice/simulations regarding concrete steps in preparing teaching modules and Pancasila student profile projects. The method used in carrying out activities is Participatory Action Research (PAR). The PKM activities were applied with lecture activities and strengthened through FGD (Focus Group Discussion) discussions and questions and answers between presenters/stakeholders and participants. The number of participants who took part in the training was 35 teachers. The results of the training show that the participants have understood and mastered the material regarding the creation of the Pancasila student profile project module and have resulted in the Pancasila student project module directly practicing the concrete steps in preparing all the documents required in the module. The training participants were very enthusiastic in taking part in this activity because it was a requirement in the independent curriculum.Keywords: development; pancasila student profile; strengtheningAbstrakPelatihan ini untuk memberikan pemahaman kepada kepala sekolah dan guru akan pentingnya pengembangan profile pelajar Pancasila yang saat ini sedang berlaku pada kurikulum merdeka. Sasaran dalam kegiatan kelompok Pengabdian Kepada Masyarakat ini yaitu para pimpinan, tenaga pendidik maupun kependidikan di SDN Oeteas Kabupaten Rote Ndao. Kegiatan dilaksanakan selama 2 Hari mulai tanggal 7–8 September 2023. Materi pokok yang disampaikan adalah untuk memberikan edukasi dan workshop lewat pendampingan pembuat proyek profile pelajar pancasila dan memberikan praktek/simulasi mengenai langkah-langkah konkrit dalam mempersiapkan modul ajar dan proyek profile pelajar Pancasila. Metode yang digunakan dalam pelaksanaan kegiatan yaitu Participatory Action Research (PAR). Kegiatan PKM tersebut, diaplikasikan dengan aktifitas ceramah dan dikuatkan melalui diskusi FGD (Focus Group Discussion) serta tanya jawab antara pemateri/stakeholders dengan peserta. Jumlah peserta yang mengikuti pelatihan sebanyak 35 orang guru. Hasil Pelatihan menunjukkan bahwa pemahaman dan penguasaan materi tentang pembuat modul proyek profile pelajar Pancasila sudah dipahami oleh peserta dan menghasil modul proyek pelajar Pancasila mempraktekkan secara langsung langkah-langkah kongkrit dalam mempersiapkan semua dokumen yang dipersyaratkan dalam modul. Para peserta pelatihan sangat antusias dalam mengikuti kegiatan ini dikrenakan menjadi tuntutan dalam kurikulum merdeka.Kata Kunci: pengembangan; profile pelajar pancasila; penguatan